THE EFFECT OF APPLICATION BASED ANDROID TO DEVELOP THE KNOWLEDGE OF PLANT IDENTIFICATION FOR BIOLOGY EDUCATION COLLEGE STUDENT - Didi Jaya Santri; Nike Anggraini; Susy Amizera (BIOEDUKASI, 2021)
Plant identification is a process of determining plant species based on classification system by observing either morphological structure or anatomical structure of the plant. The aim of this study for determine the effect of using applications on the ability to identify plants for biology education college students by comparing the identification abilities of students after carrying out plant identification activities using matching plant the characteristic of object methods and application based android. The research design used the pretest – post test group design technique. Furthermore, data analysis used N-gain test to determine the improvement of collage students' abilities and independent sample t-test to determine the effect of the use of application based android on the ability to identify plants with the prerequisite test for the normality test and homogeneity of the research sample. The results showed that there were differences in the improvement of students' abilities in plant identification activities. The data showed that the increase in knowledge in the treatment class was higher due to the use of application based android by students. The independent-sample t-test analysis showed the sig value. 0.00 (<0.05). It indicates that there is a significant difference in increasing student knowledge in plant identification activities in classes, where the experimental class shows a better improvement than the control class. Thus it can be concluded that the use of application based android affects the ability of plant identification in college students